2018
DOI: 10.1016/j.xphs.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Study the Physical Stability of Monoclonal Antibody Formulations—Dilution From a Denaturant

Abstract: The early-stage assessment of the physical stability of new monoclonal antibodies in different formulations is often based on high-throughput techniques that suffer from various drawbacks. Accordingly, new approaches that facilitate the protein formulation development can be of high value to the industry. In this study, a dynamic light scattering plate reader is used to measure the aggregation (by means of the increase in the hydrodynamic radius [R]) of monoclonal antibody samples that were subject to incubati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…We previously showed that assessing the aggregation during dilution-or dialysis-refolding from denaturants can be a valuable tool to select monoclonal antibody formulations with higher physical stability and suppressed aggregation during storage 30,37,44 . In an effort to standardize such experiments, we presented a ReFOLD assay that is based on microdialysis in deep multiwell plates 30 .…”
Section: Refoldability and Colloidal Stability Studies Provide Orthogonal Informationmentioning
confidence: 99%
“…We previously showed that assessing the aggregation during dilution-or dialysis-refolding from denaturants can be a valuable tool to select monoclonal antibody formulations with higher physical stability and suppressed aggregation during storage 30,37,44 . In an effort to standardize such experiments, we presented a ReFOLD assay that is based on microdialysis in deep multiwell plates 30 .…”
Section: Refoldability and Colloidal Stability Studies Provide Orthogonal Informationmentioning
confidence: 99%
“…An increase in hydrodynamic radius can be associated with the formation of aggregated particles. 36,37 The PDI allows to estimate the heterogeneity of this sample. For monodisperse samples a PDI ≤ 0.1 is expected.…”
Section: Resultsmentioning
confidence: 99%
“…The bulk solutions of both mAbs were buffer exchanged to 20 mM (LMU1) or 10 mM (LMU2) histidine/histidine hydrochloride with pH 5.5 at 20 °C to 25 °C using Slide-A-Lyzer™ 10,000 molecular weight cut-off dialysis cassettes (Thermo Fisher Scientific, Waltham, MA, USA). After extensive dialysis as described by Svilenov et al [ 28 ], the final buffers contained either 20 mM histidine and 0.04% ( w / v ) polysorbate 20 for LMU1 or 10 mM histidine and 0.05% ( w / v ) polysorbate 80 for LMU2. The concentration of both antibodies was measured with a Nanodrop 2000 UV spectrophotometer (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%